Children, youth and transitional justice in Northern Uganda - Luehe, Ulrike (Department of Political Studies, 2014)
With the end of the Lord’s Resistance Army conflict in northern Uganda, efforts of dealing with the violent past and paving the way for a more just, peaceful future are now taking shape in Uganda and especially the northern region. Existing frameworks and proposals for transitional justice emphasize traditional justice, the option of establishing a truth commission, formal justice and reparations most prominently. Despite the strong involvement of children and youths in the conflict – as victims and perpetrators – their inclusion in, needs for and expectations of transitional justice have barely been explored or acknowledged. This thesis thus aims at exploring ways in which formerly abducted children can be included in such processes in meaningful ways that accommodate for their needs and preferences. Since the existing research and literature on the field of child soldiers and transitional justice is rather limited, field work has been conducted in northern Uganda in November and December of 2012. A total of 17 people were interviewed representing a variety of local, national and international organizations as well as government agencies specializing in the fields of transitional justice or child protection, and rehabilitation of former child soldiers. Semistructured interviews with open-ended questions were conducted and the gathered qualitative data was used to substantiate, complement or fill gaps in the existing body of research on the topic. The findings of this thesis conclude that there is a need for comprehensive, inclusive transitional justice mechanisms that acknowledge former abductees in their dual role as victims and perpetrators. A desire for active government involvement and participation in these processes has been emphasized strongly. The research has furthermore shown the need for transitional justice mechanisms to foster agency and the empowerment of formerly abducted children and youths in order to enable them to become active, resourceful members of their communities.